Tanggung jawab koperasi simpan pinjam terhadap jaminan milik pengurus yang di jaminkan hutang koperasi - Diah Aju Wisnuwardhani (University of Merdeka Malang, 2018)
The purpose of this Cooperative is not just to seek profit merely as the purpose of another legal entity such as a Limited Liability Company. Cooperatives are economic enterprises that prioritize the welfare of their members through the financial sector. This emphasizes the importance of member welfare as one of the objectives ofestablishing a cooperative. In order for the objectives of the cooperative to be achieved, cooperatives can carry out various business activities. In connection with lending and borrowing which forms the basis of the relationship between the bank and the Savings and Loan Cooperative, the Savings and Loan Cooperative has the obligation to return when requested by the bank or when the Savings and Loan Cooperative is no longer active in its activities. Furthermore, what is the legal relationship between the Savings and Credit Cooperative and the creditor? The basis of the legal relationship between Savings and Loans Cooperatives and creditors is an agreement to borrow and borrow money which is often referred to by the community as a credit agreement. The agreement is actually a relationship based on a loan lending agreement as stipulated in Article 1754 of the Civil Code. Cooperative loans for bank financing are carried out and signed by all cooperative managers through personal quarantee as stipulated in Article 1820 of the Civil Code, namely as the guarantor of the debt referred to as the “Guarantor”. While the personal assets submitted by the management to the bank as an additional guarantee or accesoir.How to cite item: Wisnuwardhani, D. (2018). Tanggung jawab koperasi simpan pinjam terhadap jaminan milik pengurus yang di jaminkan hutang koperasi. Jurnal Cakrawala Hukum, 9(1), 21-30. doi:https://doi.org/10.26905/idjch.v9i1.2112